TINGKAT KECENDERUNGAN PERILAKU EKSTREMISME BERBASIS AKTIVITAS DIGITAL DI KALANGAN MAHASISWA - Istiqomah, Annisa; Marzuki, Marzuki; Sutrisno, Cucu; Samsuri, Samsuri; Aziz, Sulthon Abdul (Program Studi PPKn Universitas Pendidikan Ganesha, 2025)
Extremism among students can have very serious consequences. It can not only damage the image and reputation of educational institutions, but can also cause broader social damage. Violent acts carried out by students can instill fear, damage intergroup relations in society, and reduce social tensions. This study aims to 1) identify early signs of extremist behavior among students through social media; 2) Identify specific factors that encourage or reduce the tendency of extremist behavior through social media. The results of the study indicate that: 1. Overall, the level of tendency of digital-based extremist behavior among students can be considered high, because the frequency of the majority of respondents (35.10%) is in the high category. These results indicate that students are still quite vulnerable to exposure to extremist content in the digital space: 2) The tendency of digital-based extremism among students is more at the ideological and attitudinal level (loyalty, justification of violence, and rejection of diversity) than at the level of concrete actions (access, community involvement, and commitment to extreme action). In other words, students are in a phase of ideological vulnerability that requires serious attention through digital literacy programs, strengthening national understanding, and learning tolerance to prevent the development of these ideological attitudes into concrete extreme behavior.